Sustainable air dehumidification using liquid desiccant technology: performance analysis of a packed-bed system - Singh, Satwinder; Kumar, Ravinder (Frontiers in Thermal Engineering, 2025)
IntroductionDesiccant-based dehumidification is a promising energy-efficient solution for air moisture control, particularly in humid climates.MethodsThis paper aims to experimentally evaluate the performance of a counter flow packed bed dehumidifier using PVC honeycomb packing with calcium chloride solution as a desiccant. Desiccant solution flow rate, air mass flow rate, and air inlet temperature were the main input variables taken into account in the experiment.ResultsThe performance of the system was assessed by measuring the moisture removal rate, the exit air temperature, and the air’s outlet humidity ratio. Results show that increasing the air mass flow rate from 0.00074 to 0.00119 kg/s and raising the desiccant inlet temperature from 50 °C to 70 °C increases the moisture extraction rate from 0.032 × 10−4 kg/s to 0.225 × 10−4 kg/s and a corresponding rise in outlet humidity ratio.DiscussionThese outcomes contribute to the optimization of liquid desiccant dehumidifiers and hence support their broader application in energy-efficient climate control systems.